Correlation between Housing Quality and the Human Development Index in North Sumatra - Lasma Melinda Siahaan; Natasya Santa Elisabeth Siahaan (TALENTA Publisher, Universitas Sumatera Utara, 2025)
A society's housing quality is a fundamental factor in its social and economic well-being, and it is presumed to be correlated with the Human Development Index, which measures a country's development. This study seeks to analyze the relationship between various indicators of housing quality and the components of the HDI in North Sumatra. The research utilizes a quantitative approach, employing numerical data and statistical analysis. The variables for housing quality include floor area per capita, access to drinking water, source of electricity, and decent sanitation conditions. The results of the Pearson correlation test showed a strong positive relationship between all four housing quality indicators and the HDI. The correlation coefficients ranged from 0.60 to 0.71, indicating that as these housing quality factors improve, the HDI is likely to increase as well. Specifically, floor area per capita showed the strongest correlation at 0.7167859, followed by electricity source and drinking water. These findings highlight that development is an interconnected system, not a series of isolated projects. The study concludes that policymakers in North Sumatra should adopt an integrated and holistic approach, prioritizing investment in basic housing facilities as a crucial pillar for human capital development and economic competitiveness.